The roles of marginal lagoons in the maintenance of genetic diversity in the Brazilian migratory fishes Prochilodus argenteus and P. costatus - Melo, Bruno F.; Sato, Yoshimi; Foresti, Fausto; Oliveira, Claudio (Sociedade Brasileira de Ictiologia, 2013)
A bacia do rio São Francisco contém muitas espécies endêmicas, tais como Prochilodus argenteus e P. costatus, os quais têm grande importância comercial. Entretanto, informações sobre as principais áreas de recrutamento e estudos genéticos contendo uma extensa amostragem dessas espécies no rio São Francisco são escassas. Para investigar o papel das lagoas marginais na manutenção da variabilidade genética e na estruturação populacional dessas espécies, nós analisamos seis loci microssatélites em nove grupos amostrais de P. argenteus e cinco grupos amostrais de P. costatus. Nossos resultados revelaram altos níveis de variabilidade genética para ambas as espécies e valores baixos de diferenciação genética para P. argenteus (F ST = 0.008, P < 0.05) e P. costatus (F ST = 0.031, P < 0.05). Adicionalmente, valores altos de fluxo gênico combinados com a distância genética baixa sugerem a presença de uma única população para cada espécie no médio rio São Francisco. Possíveis rotas migratórias envolvendo lagoas marginais durante o período reprodutivo puderam ser detectadas, confirmando a importância das lagoas marginais no ciclo de vida dessas espécies. Nossos resultados também indicaram a necessidade de um manejo adequado dos recursos pesqueiros e a conservação das várzeas na bacia do rio São Francisco.

The rio São Francisco basin contains many endemic species, such as Prochilodus argenteus and P. costatus, which have great commercial importance. However, information about the main recruitment sites and genetic studies containing extensive sampling of these species are scarce. To investigate the roles of the marginal lagoons in the maintenance of genetic variability and in the population structure, we analyzed six microsatellite loci in nine sampling groups of P. argenteus and five sampling groups of P. costatus. Our results showed high levels of genetic variability and low values of genetic differentiation for P. argenteus (F ST = 0.008, P < 0.05) and for P. costatus (F ST = 0.031, P < 0.05). In addition, high values of gene flow combined with a small genetic distance suggest the presence of a single population for each species in the middle rio São Francisco basin. Moreover, putative migration routes involving marginal lagoons during the reproductive season could be detected, confirming the importance of these nurseries in the lifecycle of these species. Our results also indicate the necessity of adequate management of the fish resources and the conservation of the floodplains in the rio São Francisco basin.
Keywords: Conservation genetics; Fish migration; Microsatellite; Nursery area; Rio Sao Francisco basin